Komparácia finančnej autonómie samosprávnych jednotiek v SR - Balážová, Emília (Univerzita Pardubice, 2011)
This contribution is aimed at comparing fiscal autonomy of self-governing units after fiscal decentralization in the Slovak republic. Evaluated and compared are budgets of selected Slovakian towns with the accent on the budget incomes creation. The contribution evaluates the level of self-financing as the share of own incomes to current expenditure, and also the level of self-sufficiency as the share of own incomes (including local taxes and fees) to total incomes.
Keywords: fiscal decentralization; financial autonomy; budget incomes and expenditures